2021
DOI: 10.3389/fonc.2021.680807
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Attention Convolutional Neural Network for Liver Tumor Segmentation

Abstract: PurposeAccurate segmentation of liver and liver tumors is critical for radiotherapy. Liver tumor segmentation, however, remains a difficult and relevant problem in the field of medical image processing because of the various factors like complex and variable location, size, and shape of liver tumors, low contrast between tumors and normal tissues, and blurred or difficult-to-define lesion boundaries. In this paper, we proposed a neural network (S-Net) that can incorporate attention mechanisms to end-to-end seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…For more details on HN-Net and the attention model we adopted, please refer to our previous work. 34,35 In the fine-tuning process, we selected the top 30% of the uncertainty images to retrain the model. When we selected the top 60% or 90% of uncertainty images, it is found that the DSC values showed a minor performance improvement, while the training time escalated significantly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For more details on HN-Net and the attention model we adopted, please refer to our previous work. 34,35 In the fine-tuning process, we selected the top 30% of the uncertainty images to retrain the model. When we selected the top 60% or 90% of uncertainty images, it is found that the DSC values showed a minor performance improvement, while the training time escalated significantly.…”
Section: Discussionmentioning
confidence: 99%
“…CBAM is able to infer from two different dimensions (spatial and channel dimensions) for the same input, leading to improved feature aggregation and semantic reasoning. For more details on HN‐Net and the attention model we adopted, please refer to our previous work 34,35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, deep learning has provided promising solutions for many data-driven clinical challenges (Protonotarios et al 2022, Wang et al 2022a, Luan et al 2021. As a result, an increasing number of deep learning-based commercial artificial intelligence software (DL-CAIS) are being introduced into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, RT planning involves manual delineation of target and OARs on CT images, which necessitates the expertise of physicians, a process that is both labor-intensive and time-consuming (Xu et al 2022). Nowadays, computer-assisted medical diagnosis has evolved into a prevalent tool, enhancing the capabilities of lesion detection, diagnosis, and segmentation (Luan et al 2021, Zhang et al 2021a, Luan et al 2023a. Despite the comprehensive research conducted on automatic H&N segmentation, the absence of precise delineation for H&N OARs and the limitation of using single dataset in model training have contributed to deficiencies in the robustness of automatic segmentation algorithms (Gao et al 2019, Liang et al 2020.…”
Section: Introductionmentioning
confidence: 99%